2015
DOI: 10.1021/acs.nanolett.5b01358
|View full text |Cite
|
Sign up to set email alerts
|

Robust Topological Interfaces and Charge Transfer in Epitaxial Bi2Se3/II–VI Semiconductor Superlattices

Abstract: Access to charge transport through Dirac surface states in topological insulators (TIs) can be challenging due to their intermixing with bulk states or nontopological two-dimensional electron gas (2DEG) quantum well states caused by bending of electronic bands near the surface. The band bending arises via charge transfer from surface adatoms or interfaces and, therefore, the choice of layers abutting topological surfaces is critical. Here we report molecular beam epitaxial growth of Bi2Se3/ZnxCd1–xSe superlatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…MBE-grown films have a number of advantages over exfoliated films, including large area growth and the ability to controllably dope the materials, resulting in recent observations of the quantum anomalous Hall effect [22][23][24][25][26][27]. Unfortunately, both bulk crystals and thin films tend to exhibit significant conductivity from non-topological electrons, either from bulk states and/or from surface accumulation layers [28,29]. This is a particular problem for electrical measurements and applications, as the electrical signal from the non-topological electrons can overwhelm the signal from the surface states even in very thin films.…”
Section: Crystal Structurementioning
confidence: 99%
See 2 more Smart Citations
“…MBE-grown films have a number of advantages over exfoliated films, including large area growth and the ability to controllably dope the materials, resulting in recent observations of the quantum anomalous Hall effect [22][23][24][25][26][27]. Unfortunately, both bulk crystals and thin films tend to exhibit significant conductivity from non-topological electrons, either from bulk states and/or from surface accumulation layers [28,29]. This is a particular problem for electrical measurements and applications, as the electrical signal from the non-topological electrons can overwhelm the signal from the surface states even in very thin films.…”
Section: Crystal Structurementioning
confidence: 99%
“…They reported that Zn0.49Cd0.51Se and Zn0.23Cd0.25Mg0.52Se layers had improved quality relative to ZnSe. Another work by the same group reported that in MBE grown Zn0.49Cd0.51Se/Bi2Se3 superlattices, a single topological Dirac cone per TI layer was realized [28]. Leveraging the wide In addition to band insulators, II-VI semiconductor layers have also been grown in combination with TI materials.…”
Section: Heterostructures and Superlatticesmentioning
confidence: 99%
See 1 more Smart Citation
“…17,[19][20][21][22] The characteristics of the gapless boundary states are linear dispersion in the bulk band gap, spin-texture, robustness against scattering by nonmagnetic impurities, and symmetry protection. Studies have demonstrated that the formation of heterostructures, [23][24][25][26] alloying, 20,27 and thickness engineering 28 have advantages for controlling the electronic properties of TIs. In addition, recent studies show that it is possible to observe novel properties in TI superlattices, such as both time-reversal and crystal symmetry protected surface states, 29,30 band structure tuning through a topological phase transition, 31 topologically nontrivial surface states in a magnetic-TI/TI superlattice, 32 and the realization of 3D Weyl semimetal phases. 33 To fully exploit TIs in future devices, a detailed exploration of TI heterostructures/superlattices is needed.…”
Section: Introductionmentioning
confidence: 99%
“…While initial research efforts had mostly been devoted to the vacuum-facing TI surfaces [29][30][31][32][33][34][35] , increasing experimental [36][37][38][39] and theoretical attention [40][41][42][43][44] have recently been paid to the more realistic situation, the interfaces between TIs and normal insulators (NIs). It is motivated by the fact that interfaces are protected from the possible ambient contamination 45,46 and moreover these types of heterojunctions can be integrated into existing semiconductor technology, hence, they are more advantageous for utilizing the topological conducting boundary states.…”
Section: Introductionmentioning
confidence: 99%